Level of understanding towards biology terms on biology education students' of IAIN Kerinci - Wahyuni Wahyuni; Ramadani Ramadani; Tiara Tiara (Journal on Biology and Instruction, 2021)
Biology is one of the fields of study that demands a high ability to think in understanding the subject matter contained in it, in this case scientific reading and good thinking skills become very important. This is because in biology learning there are many tables, diagrams and drawings, so it needs a special ability to understand it. Therefore, it is necessary to improve students' thinking skills in order to achieve optimal learning outcomes, because the ability to think will be the basic capital in improving other abilities. The research aims to determine the level of understanding of IAIN Kerinci students on terms in Biology and to know what factors influence the understanding of IAIN Kerinci Biology Tadris students in understanding terms in Biology. The population in this study was 975 students majoring in Tadris Biology IAIN Kerinci while the sample in this study was 50 students of semester 1 (one) majoring in Tadris Biology IAIN Kerinci. Based on the results of the study that the author conducted in semester 1 (one) majoring in Tadris Biology IAIN Kerinci obtained that through the test of matching the level of understanding of students more dominantly obtained a score below 54 with a percentage of 54%. Meanwhile, through the essay test, the level of understanding of students is more dominant in obtaining at â‰¤ 54 with a percentage of 90%. And for factors that affect the understanding of students obtained a percentage that is more dominant on the indicator of emotional intelligence that is with a percentage of 76.8 %. In the indicator of intellectual intelligence obtained a percentage of 72.3 % while in the indicator of learning obtained a percentage value of 73.2 %, and in the indicator of learning behavior obtained the lowest percentage value of 62.8 %.